General anesthesia for cesarean delivery and childhood neurodevelopmental and perinatal outcomes: a secondary analysis of a randomized controlled trial. (February 2021) - Robbins, L.S.; Blanchard, C.T.; Biasini, F.J.; Powell, M.F.; Casey, B.M.; Tita, A.T.; Harper, L.M.
Highlights: Few data on neurologic outcomes after in utero exposure to general anesthesia (GA). Secondary analysis of randomized trial of maternal magnesium and cerebral palsy. Exposure to GA was not associated with impaired neurodevelopment overall. Only severe motor delay was significantly more common among infants exposed to GA. Findings are reassuring regarding a single, short in utero exposure to GA. Abstract: Background: In 2016, the U.S. Food and Drug Administration expressed concern that neurodevelopment may be negatively affected by anesthesia or sedation exposure in pregnancy or before three years of age. We examined the association between general anesthesia at the time of cesarean delivery and early childhood neurodevelopment. Methods: A secondary analysis of a multicenter randomized controlled trial assessing magnesium for prevention of cerebral palsy in infants at risk for preterm delivery. Exposure was general compared to neuraxial anesthesia. The primary outcome was motor or mental delay at two years of age, assessed by Bayley Scales of Infant Development II (BSIDII). Secondary outcomes included BSIDII subdomains and perinatal outcomes. Multivariable logistic regression models were performed to control for confounders. Results: Of 557 women undergoing cesarean delivery, 119 (21%) received general anesthesia. There were no differences in the primary composite outcome of developmental delay (aOR 0.93, 95% CI 0.61 to 1.43) or the BSIDII subdomains of mild, moderate, or severe mental delay, or mild or moderate motor delay. Severe motor delay was more common among infants exposed to general anesthesia (aOR 1.98, 95% CI 1.06 to 3.69). Infants exposed to general anesthesia had longer neonatal intensive care stays (51 vs 37 days, P =0.010). Conclusions: General anesthesia for cesarean delivery was not associated with overall neurodevelopmental delay at two years of age, except for greater odds of severe motor delay. Future studies should evaluate this finding, as well as the impact on neurodevelopment of longer or multiple anesthetic exposures across all gestational ages.